KAJIAN TINGKAT PENCEMARAN UDARA OLEH GAS NH3 DAN H2S PADA PROSES PENGOMPOSAN SECARA AEROB - Setiyo, Yohanes (Agrotekno, 2007)
This  research  objective  was  to  know the  level  polutan  of NH3and  H2S  from  aerobic  composting  process.  Modified  Briski method  was  use  to  identification NH3 and   H2S.  Pada  metode Briski  et al. (2003)  tidak  ada  pengukuran  gas  NH3 and  H2S. Both  polutan  were  colect  at  solvent  BaCL2 and  H2SO4 0.1  N along  one  week,  than  the  level  of    concentration  at  air  were identificated by chromatography method. The level concentration of NH3 at the air was 0.092 ppm to 0.25 ppm, and the level polutan of H2S to the air  was 0.3 ppm to 1.1 ppm. Both polutan were below from standard of SNI.